Phylogenomics of Marine Algae - Cheong, Xin Chan (Malaysian Journal of Science, 2013)
De novo genome and transcriptome data from a number of marine algal species have recently become available, ranging from red, green and brown algae, as well as other photosynthetic eukaryotes, e.g. diatoms and dinofl agellates. Phylogenomic approaches are widely adopted to decipher the evolutionary relationships among diverse lineages. Novel algal genomes therefore provide an exciting analysis platform for understanding algal biology, ecophysiology and diversity, and at a broader scale, eukaryote evolution. In this brief communication, I highlight major fi ndings from recent phylogenomic studies of marine algae and their impact to the research fi eld. I then discuss the current trends and future directions of phylogenomics, and how we can apply this approach in studying biodiversity in the South China Sea. (Keywords: algal genomics, biodiversity, endosymbiosis, lateral genetic transfer, marine algae, phylogenomics)